Antioxidants and Ageing - Biswaranjan Paital; Tallat Jahan; Sthiti pragyan Priyadarshini; Ankita Mohanty (Open Journal of Environmental Biology - Peertechz Publications, 2017)
Antioxidants are the molecules that reduce the chance of ageing by diminishing or maintaining the level of oxidants with or without free radical activity. Therefore, to many people, "antioxidants" and "anti-aging" go hand-in-hand. Antioxidants can be supplied with dietary supplements for body, or can be used in osmetics for skin, can be touted as the antidote to cell-damaging free radicals and finally, they act as the key to long-lasting youth. Although, present study reveals a complicated relation between aging and antioxidants, the rate of ageing is predicted to be more important than lifespan.Therefore, in a life span, slowing the process of ageing is more important.